2022
DOI: 10.1186/s12903-022-02493-8
|View full text |Cite
|
Sign up to set email alerts
|

What is the prevalence of peri-implantitis? A systematic review and meta-analysis

Abstract: Background Peri-implantitis is a usual finding but estimates of its prevalence fluctuate very much. This may be due to the wide variety of disease definitions. This systematic review aims to estimate the overall prevalence of peri-implantitis and the effect of different study designs, function times and use of probing depth on prevalence rate. Methods Following electronic and manual searches of the literature published from January 2005 to December… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 87 publications
0
14
0
Order By: Relevance
“…Peri‐implantitis is now defined as a pathological condition that occurs in tissues around dental implants and is characterized by inflammation in the peri‐implant mucosa and progressive loss of supporting bone (Figure 1). 6 In a recent systematic review by Diaz and Gonzalo et al, 7 57 studies were included for meta‐analysis and the prevalence of peri‐implantitis was about 19.53% at the patient‐level and 12.53% at the implant‐level but the result remains highly variable depending on the case definition. The authors concluded for future studies that are essential to have standardized measurement and diagnostic criteria to access the true prevalence.…”
Section: Diagnosis and Etiology Of Peri‐implant Diseases And Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peri‐implantitis is now defined as a pathological condition that occurs in tissues around dental implants and is characterized by inflammation in the peri‐implant mucosa and progressive loss of supporting bone (Figure 1). 6 In a recent systematic review by Diaz and Gonzalo et al, 7 57 studies were included for meta‐analysis and the prevalence of peri‐implantitis was about 19.53% at the patient‐level and 12.53% at the implant‐level but the result remains highly variable depending on the case definition. The authors concluded for future studies that are essential to have standardized measurement and diagnostic criteria to access the true prevalence.…”
Section: Diagnosis and Etiology Of Peri‐implant Diseases And Conditionsmentioning
confidence: 99%
“…The Implant Disease Risk Assessment (IDRA) is a tool proposed by Heitz-Mayfield in 2020 130 for the prevention of peri-implant disease. The IDRA involves the assessment of eight parameters, including (1) history of periodontitis, (2) percentage of sites with bleeding on probing, (3) prevalence of probing depths more than 5 mm, (4) periodontal bone loss in relation to patient's age, (5) periodontitis susceptibility, (6) supportive periodontal therapy, (7) proximity of restorative margin to bone crest, and (8) implant prosthesis related factors. Scores for each parameter can be calculated to identify a patient's individual risk of developing peri-implantitis.…”
Section: Preventive Measures For Peri-implant Diseasesmentioning
confidence: 99%
“…Peri-implantitis (PI) is defined as an inflammatory lesion in the tissues surrounding the implant with progressing of bone loss beyond the expected physiologic bone remodeling. 1,2 PI is the most common complication in implant dentistry, 3,4 affecting around 20% of patients [5][6][7] and 13% of implants, 6,7 with study results ranging widely.…”
Section: Introductionmentioning
confidence: 99%
“…Dental implants are the preferred fixed oral rehabilitation for replacing lost teeth. With their increasing popularity, peri-implant tissue diseases have also increased, with an estimated prevalence of 19.5% [ 1 ]. Peri-implantitis is a condition of the tissues surrounding dental implants characterised by an inflammatory response of the peri-implant connective tissue caused by dysbiotic plaque.…”
Section: Introductionmentioning
confidence: 99%